2020
DOI: 10.1002/spp2.1295
|View full text |Cite
|
Sign up to set email alerts
|

Brachiopods from the Byrd Group (Cambrian Series 2, Stage 4) Central Transantarctic Mountains, East Antarctica: biostratigraphy, phylogeny and systematics

Abstract: Brachiopods from Cambrian Series 2, Stage 4 carbonate strata of the Byrd Group in the Central Transantarctic Mountains, East Antarctica, are described for the first time. These include six lingulate, one paterinate and one rhynchonelliform taxon, including the new lingulate brachiopod Plicarmus wildi gen. et sp. nov. The biostratigraphy correlates closely to the brachiopods recently reported from the Xinji Formation (Shuiyu section) in North China, as well as brachiopods recovered from the Dailyatia odyssei Zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 52 publications
3
23
0
Order By: Relevance
“…This also revealed that Palaeotreta zhujiahensis experienced three stages during the entire ontogenetic sequence, which can be well compared with the almost coeval E. zhenbaensis ( Fig. 10; Z.-L. Zhang et al 2018a;Claybourn et al 2020). When compared to the ontogeny of E. zhenbaensis, however, only two ontogenetic stages (T1-T2) can be distinguished during the growth of P. shannanensis (Figs 2, 6, 7).…”
Section: Ontogenetic Development Of Palaeotretamentioning
confidence: 66%
See 3 more Smart Citations
“…This also revealed that Palaeotreta zhujiahensis experienced three stages during the entire ontogenetic sequence, which can be well compared with the almost coeval E. zhenbaensis ( Fig. 10; Z.-L. Zhang et al 2018a;Claybourn et al 2020). When compared to the ontogeny of E. zhenbaensis, however, only two ontogenetic stages (T1-T2) can be distinguished during the growth of P. shannanensis (Figs 2, 6, 7).…”
Section: Ontogenetic Development Of Palaeotretamentioning
confidence: 66%
“…Compared with the other two species P. zhujiahensis and E. zhenbaensis (Z.-L. Zhang et al 2018a), P. shannanensis has a more restricted distribution and lower abundance, which may indicate this ancestral acrotretide was not suited to life in distal mixed clastic platforms. By contrast, E. zhenbaensis has more derived characters exemplified by faster growth rates during accretionary shell growth, especially during stage T3, enabling a wider geographical distribution and increased abundance in shallow carbonate environments (Li & Holmer 2004;Betts et al 2017;Z.-L. Zhang et al 2018a;Claybourn et al 2020). The evidence presented here suggests evolutionary modification to ontogenetic changes resulted in the early divergence of Palaeotreta and Eohadrotreta, and played an important role in the early evolution of acrotretides.…”
Section: Phylogenetic Implicationsmentioning
confidence: 72%
See 2 more Smart Citations
“…By the Devonian, this group diminished and finally went extinct (Bassett et al, 1999; Holmer and Popov, 2000). Our present knowledge of Cambrian acrotretoid brachiopods is largely based on material obtained by dissolving carbonate rocks in Kazakhstan, Scandinavia, the Ural Mountains (Popov and Holmer, 1994; Holmer et al, 2001), United States (Streng and Holmer, 2006), Canada (Robson et al, 2003), Antarctic (Holmer et al, 1996; Claybourn et al, 2020), Morocco (Streng, 1999), south Australia (Betts et al, 2017, 2019), Himalaya (Popov et al, 2015), and China (Li and Holmer, 2004; Zhang et al, 2016; Pan et al, 2019). These acrotretoid faunas are well preserved in three-dimension, including fine details of ornamentation and delicate shell structures.…”
Section: Introductionmentioning
confidence: 99%